Development and application of new modified poly(styrene-divinylbenzene) adsorbents and chromatography stationary phases -volume 1 (PS-DVB heptadecyl ketone, chloromethyl PS-DVB, and octadecoxy methyl PS-DVB) - Sanagi, Mohd. Marsin; Abu Naim, Ahmedy; Hussain, Asiah; Siregar, Sri Hilma; Sarjadi, Mohd. Sani; Abd. Aziz, Norsyariza (Universiti Teknologi Malaysia, 2005)
Poly(styrene-divinyl benzene) (PS-DVB) resin is an attractive adsorbent for extraction and separation of various types of compounds due to its stability over the pH range of 1-14. However, PS-DVB resin is known to have hydrophobic surfaces that highly retain non-polar compounds while poorly retain polar compounds. To improve its use in the separation or extraction of polar compounds, PS-DVB resin must be chemically or physically bonded to hydrophilic groups to reduce its hydrophobic surface. The objectives of this project were to modify PS-DVB phases by introducing moieties that can increase the dispersive forces and lower the hydrophobicity of the PS-DVB phases and to examine the characteristics and applications of the modified PS-DVB adsorbents. The PS-DVB adsorbents were prepared by suspension polymerization method with polyvinyl alcohol as the suspension stabilizer at a stirring speed of 1000 rpm for 20 h. In the first approach (Volume 1), the synthesized PS-DVB adsorbents were subjected to modifications that consisted of (i) Friedel-Crafts acylation reaction using stearoyl chloride as an acylation agent to produce PS-DVB heptadecyl ketone, (ii) Chloromethylation reaction to produce chloromethyl PS-DVB in the presence of chloromethyl styrene, and (iii) Williamson ether reaction using sodium metal and octadecanol as reaction agents to produce octadecoxy methyl PS-DVB. The synthesized adsorbents were characterized by FTIR spectroscopy, SEM, nitrogen adsorption analysis and thermogravimetric analysis. Solid phase extraction (SPE) studies of test compounds, namely nitrobenzene, 2- chlorophenol, benzaldehyde, butyrophenone, and p-cresol were carried out using SPE tubes packed with the synthesized adsorbents. The recoveries obtained for the home-made PS-DVB were in the range of 7% to 72% with relative standard deviations of 1% to 10%. Increased percentages of recovery (35%-83%) with the relative standard deviations of 2%-7% were obtained using PS-DVB heptadecyl ketone. Highest recovery percentages (67%-100%) were obtained using commercial C18-silica adsorbent. Highest breakthrough volume was achieved for PS-DVB heptadecyl ketone adsorbent, i.e. 30.60 mL of 20 ppm nitrobenzene and 20.47 mL of 20 ppm 2-chlorophenol. Lowest breakthrough volume was obtained for octadecoxy methyl PS-DVB adsorbent (1.03 mL of 20 ppm nitrobenzene and 1.00 mL of 20 ppm 2-chlorophenol). PS-DVB heptadecyl ketone has been proven suitable to be used as SPE adsorbent in the future.